An international review of the development and implementation of shared print storage - Genoni, Paul (Australian Library and Information Association, 2013)
Abstract: This article undertakes a review of the literature related to shared print storage and national repositories from 1980 – 2013. There is a separate overview of the relevant Australian literature. The coverage includes both relevant journal literature and major reports. In the process the article traces the developments in the theory and practice of shared print storage as the rapid emergence of digital content and services became apparent. This includes the increasingly broad-scale that has emerged in the planning for future print storage. Note is also taken of the paucity of research based evidence, and the discrepancies between the literature representing the interests of professional bodies with supra-regional responsibilities and the (sometimes) lack of activity or engagement by managers of individual collections.